Implementation of the Use of Authentic Assessments for Biology Teachers in Public High Schools in Makassar City - Adawiyah, Ridhoyatul; Nurhayati B, Nurhayati B; Tayieb, Mushawwir (Biology Teaching and Learning, 2023)
Abstract. This study is a quantitative descriptive research that aims to examine the Biology teachers’ perception on authentic assessment in SMAN (public senior high schools), the implementation of authentic assessment in Biology learning, and the inhibiting factors of Biology teachers in implementing authentic assessment at SMAN in Makassar City. The research population were 23 SMAN in Makassar City. Of the 23 schools, only 16 schools had teachers willing to be respondents or the sample of the study with the total of 35 Biology teachers at SMAN in Makassar city. Data collection techniques employed observation, questionnaires, and interviews. The results of the study reveal that the Biology teachers’ perception on authentic assessment is categorized as Very Good, while the implementation of authentic assessment by Biology teachers at SMAN in Makassar City which includes the cognitive, affective, and psychomotor domains is categorized as Very Good as well, where the teachers assess the knowledge competency by giving written and oral assignments to students, in the affective domain the Biology teachers at SMAN in Makassar City assess each student during and after learning, and in the psychomotor domain the teachers conducts an assessment by giving project assignments, portfolios, and products to students both individually and in groups. The inhibiting factors encountered by Biology teachers in authentic assessment overall have similarities, namely limited time in assessing, lack of students’ motivation in learning, and lack of availability of facilities and infrastructure in Biology Laboratory.Keywords: Authentic Assessment, Perception, Assessment Implementation, Assessment Inhibiting Factors